Mathematical modelling and numerical optimisation of machining parameters for the CNC end milling process using response surface methodology. (2017) - Chowdary, Boppana V.; Kisraj, Mitra; Ojha, Kuldeep; Ali, Fahraz
This study applies response surface methodology (RSM) to optimise the machining parameters for minimum surface roughness in the end milling process for 5083 aluminium workpiece using high-speed steel cutting tools. The combination of parameters investigated and varied in this research work was spindle speed, feed rate, depth of cut and diameter of tool. The central composite design method was used to reduce the number of experimental runs, whereas modelling and analysis with RSM were performed to obtain the objective function for surface roughness. Furthermore, optimisation of the objective function for surface roughness was performed. The results indicated that the determined optimal combination of machining parameters improved the performance of the machining process.